ORGANIZING VARIOUS GAMES FOR TEACHING ENGLISH - Eshtayeva Dildora Kahharovna (Web of Journals Publishing, 2024)
This article presents modern methods of teaching English to preschool children. Since English is becoming the universal language of the world, teaching it from an early age is vital. The article provides insights into this approach.
Keywords: Foreign language, language portfolio interactivity, Last Man Standing activities, riddles.